Effect of arsenic treatments on physiological parameters of sunflower and maize plants - Várallyay, Szilvia; Veres, Szilvia; Garousi, Farzaneh; Bódi, Éva; Kovács, Béla (Acta Agraria Debreceniensis, 2015)
The environment is contaminated with heavy metals and other toxic compounds. One of the most important toxic element is the arsenic (As). The objective of our study was to investigate the effect of As on fresh and dry weight of sunflower and maize in the early growth phases. Seedlings were grown in climate room on nutrient solution which were treated with 3, 10 and 30 mg kg-1 arsenic. The plants were treated separately with As(III) and As(V). After 14 day, changes in fresh and dry weight of maize shoots and roots were recorded. In the case of sunflower these parameters were measured after 21 day. The applied As(III) and As(V) decreased the fresh and dry mass of the shoots and roots of seedlings, especially at concentration 30 mg kg-1. We can draw the conclusion that the treatments of the maize and sunflower roots with arsenic had negative effects on the biomass accumulation. We found that the sunflower plants are more sensitive to arsenic toxicity than maize plants, and all data demonstrate that the As(III) is more toxic to these plants than the As(V).